2017
DOI: 10.12988/ces.2017.79109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transpiration in post-post-state condition on the agroindustrial quality of Chrysobalanus icaco L fruit variety

Abstract: The effect of post-harvest transpiration on the agroindustrial quality of the fruit of Chrysobalanus Icaco rosa variety was determined. The methodology followed allowed to find the loss of water for 11 days after its collection and the specific characteristics of color, size and physical appearance, to determine shelf life and its usefulness as raw material. To look at the effect caused by dehydration, a simple linear regression model was fitted using SPSS statistical software to observe, analyze and correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Concerning the water activity, the value found for the C. icaco fruits from BA and RN showed their potential for degradability and susceptibility to deterioration by microorganisms [ 5 ] and consequent loss of firmness. In their post-harvest study with in natura C. icaco fruits from the region of Cartagena, Colombia, Diaz-Gomez et al [ 27 ] found a shelf life of three days at an average temperature of 28 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the water activity, the value found for the C. icaco fruits from BA and RN showed their potential for degradability and susceptibility to deterioration by microorganisms [ 5 ] and consequent loss of firmness. In their post-harvest study with in natura C. icaco fruits from the region of Cartagena, Colombia, Diaz-Gomez et al [ 27 ] found a shelf life of three days at an average temperature of 28 °C.…”
Section: Discussionmentioning
confidence: 99%
“…The Bay of Cartagena is located in the central part of the Colombian Caribbean, between latitude 10 ∘ 26 ′ − 10 ∘ 16′ N and longitude 75 ∘ 30 ′ − 75 ∘ 36 ′ . This body of water has an approximately area of 82 2 and an average depth of 16 . It is the main component of the marine system of Cartagena and its origin is attributed to the formation of natural coral barriers that extended parallel to the coast and consolidated towards the end of the Upper Quaternary period [2,12].…”
Section: Study Areamentioning
confidence: 99%
“…This body of water has an approximately area of 82 2 and an average depth of 16 . It is the main component of the marine system of Cartagena and its origin is attributed to the formation of natural coral barriers that extended parallel to the coast and consolidated towards the end of the Upper Quaternary period [2,12]. The Canal del Dique, converted into a component of the Magdalena River fluvial system, generated the greatest morphological changes in the bay enclosure by introducing additional sedimentological elements, which very quickly weakened the coral life inside the system.…”
Section: Study Areamentioning
confidence: 99%
“…In the Colombian Caribbean coast, there is a wide variety of crops, among which are some legumes, one of these species is the Zaragoza Bean, its nutritional properties and the way of consumption are very similar to those of the Common Bean, and it becomes in an alternative for use in the food industry [3]. Although its production is very reduced due to the rural exodus and the change of peasant customs; however, work has been developed for the recovery of this species [4].…”
Section: Introductionmentioning
confidence: 99%